Pengaruh Tarif Progresif, Kualitas Pelayanan, Sosialisasi Perpajakan dan Pengetahuan Perpajakan Pada Kepatuhan Wajib Pajak - Wijayanti, Luh Putu Cintya; Sukartha, I Made (E-Jurnal Akuntansi, 2018)
Tax is the largest source of revenue for country, especially Indonesia. In achieving the level of tax compliance and maintaining the level of compliance is an issue of concern in both developed and developing countries. This research was conducted at the SAMSAT Office Bangli Regency by using a sample size of 397 people with stratified random sampling method that is by observing the level (strata) on the population element. The data analysis technique used in this study is the multiple linear regression analysis. The results of the study found that progressive rates had positive effect on taxpayer compliance. Service quality has positive effect on taxpayer compliance. Taxation socialization has positive effect on taxpayer compliance. Knowledge of taxpayer taxation has positive effect on taxpayer compliance. This research is expected to be a motivation for the samsat office to be able to improve physical and non-physical facilities to improve taxpayer compliance. Keywords: progressive tariffs, service quality, tax socialization, taxpayer knowledge, compliance